2020
DOI: 10.1096/fj.201902546rr
|View full text |Cite
|
Sign up to set email alerts
|

Morinda officinalis oligosaccharides ameliorate depressive‐like behaviors in poststroke rats through upregulating GLUT3 to improve synaptic activity

Abstract: Poststroke depression (PSD) is one of the most common psychiatric diseases afflicting stroke survivors, yet the underlying mechanism is poorly understood. The pathophysiology of PSD is presumably multifactorial, involving ischemia‐induced disturbance in the context of psychosocial distress. The homeostasis of glucose metabolism is crucial to neural activity. In this study, we showed that glucose consumption was decreased in the medial prefrontal cortex (mPFC) of PSD rats. The suppressed glucose metabolism was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 63 publications
(84 reference statements)
1
18
0
Order By: Relevance
“…This study was performed under the Institutional Guidelines of the Animal Care and Use Committee, Huazhong University of Science and Technology. To produce the PSD model, transient middle cerebral artery occlusion (tMCAO) operation was performed on Male Sprague-Dawley rats (250-280 g) in accordance with previously described procedures [7]. The lament was withdrawn for reperfusion after 2 hours of tMCAO.…”
Section: Establishment Of Psd Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…This study was performed under the Institutional Guidelines of the Animal Care and Use Committee, Huazhong University of Science and Technology. To produce the PSD model, transient middle cerebral artery occlusion (tMCAO) operation was performed on Male Sprague-Dawley rats (250-280 g) in accordance with previously described procedures [7]. The lament was withdrawn for reperfusion after 2 hours of tMCAO.…”
Section: Establishment Of Psd Modelmentioning
confidence: 99%
“…Immuno uorescence was performed as described [7]. The rats' brains were xed with 4% paraformaldehyde and then cut into 20 mm sections.…”
Section: Immuno Uorescencementioning
confidence: 99%
See 1 more Smart Citation
“…Immunofluorescence was performed as previously described. 7 The rats' brains were fixed with 4% paraformaldehyde and then cut into 20-mm sections. The following primary antibodies were used:…”
Section: Immunofluorescencementioning
confidence: 99%
“…4 However, SSRI administration raises the risk of cerebral hemorrhage and other side effects. 5 It has been suggested that brain-derived neurotrophic factor (BDNF) plays an important role in the pathophysiological mechanisms of PSD. 6 Decreased concentration of serum BDNF has been demonstrated in patients with PSD.…”
Section: Introductionmentioning
confidence: 99%